Courses
Courses for Kids
Free study material
Offline Centres
More
Store

# The point (2,1) is translated parallel to the line L : x – y = 4 by $2\sqrt 3$units. If the new point Q lies in the third quadrant, then the equation of the line passing through Q and perpendicular to L is$A.2x + 2y = 1 - \sqrt 6 \\ B.x + y = 3 - 3\sqrt 6 \\ C.x + y = 3 - 2\sqrt 6 \\ D.x + y = 2 - \sqrt 6 \\$

Last updated date: 13th Jun 2024
Total views: 411.6k
Views today: 12.11k
Verified
411.6k+ views
Hint: Draw the line x –y = 4 and with the help of slope and distance formula we can find the value of Q. With the point Q and it is given that the line is perpendicular to x –y =4, we can find the required equation using slope point formula.

Lets sketch the line x – y =4. Let the point (2 ,1) be P.
It is given that PQ is parallel to the x – y = 4.
Now let's draw the graph with the above details

Step 2:
Let the new point be Q(a,b)
Now from the diagram , we can see that AQ is parallel to the given line.
The slope of the given line is 1
And since AQ is parallel , their slopes are equal
Therefore slope of AQ is 1
$\Rightarrow \dfrac{{{y_2} - {y_1}}}{{{x_2} - {x_1}}} = 1 \\ \Rightarrow \dfrac{{1 - b}}{{2 - a}} = 1 \\ \Rightarrow 1 - b = 2 - a \\ \Rightarrow a - b = 1 \\ \Rightarrow a = 1 + b \\$
Let the above equation be equation (1)
Step 3:
It is also given that P(2 , 1) is at a distance of$2\sqrt 3$ units from Q
Distance between two points is given by
$\Rightarrow \sqrt {{{({x_1} - {x_2})}^2} + {{({y_1} - {y_2})}^2}}$
Here we already know that the distance between P and Q is $2\sqrt 3$ units
Therefore ,
$\Rightarrow \sqrt {{{(2 - a)}^2} + {{(1 - b)}^2}} = 2\sqrt 3 \\ \\$
Squaring on both sides we get,
$\Rightarrow {(2 - a)^2} + {(1 - b)^2} = {(2\sqrt 3 )^2}$
Lets substitute equation (1) in the above equation
$\Rightarrow {(2 - (1 + b))^2} + {(1 - b)^2} = 4*3 \\ \Rightarrow {(1 - b)^2} + {(1 - b)^2} = 12 \\ \Rightarrow 2{(1 - b)^2} = 12 \\ \Rightarrow {(1 - b)^2} = 6 \\ \Rightarrow 1 - b = \pm \sqrt 6 \\ \Rightarrow b = 1 \pm \sqrt 6 \\$
Substitute the value of b in equation (1)
$\Rightarrow a = b + 1 \\ \Rightarrow a = 1 \pm \sqrt 6 + 1 = 2 \pm \sqrt 6 \\$
Step 4:
Here we have $a = 2 \pm \sqrt 6$ and $b = 1 \pm \sqrt 6$
Since the point Q lies in the third quadrant both the coordinates should be negative .
So $a = 2 - \sqrt 6$and $b = 1 - \sqrt 6$
Step 5:
Now we need to find the equation of the line passing through Q and perpendicular to x – y =4
Slope of x –y=4 is 1
Since our required equation is perpendicular to x –y=4.
The slope of our required line is -1
By using slope point formula
$(y - {y_1}) = m(x - {x_1})$
We have
$\Rightarrow \left( {y - (1 - \sqrt 6 )} \right) = - 1\left( {x - (2 - \sqrt 6 )} \right) \\ \Rightarrow \left( {y - 1 + \sqrt 6 } \right) = - 1\left( {x - 2 + \sqrt 6 } \right) \\ \Rightarrow y - 1 + \sqrt 6 = - x + 2 - \sqrt 6 \\ \Rightarrow x + y = 2 - \sqrt 6 + 1 - \sqrt 6 \\ \Rightarrow x + y = 3 - 2\sqrt 6 \\$
Therefore the required equation is $x + y = 3 - 2\sqrt 6$
The correct option is C.

Note:1. Slope of parallel lines are equal.
2.Product of the slope of perpendicular lines is -1.
3.In a graph, there are four quadrants based on the sign of x and y coordinate. In the first quadrant both x and y are positive and in the second quadrant x is negative and y is positive , in the third quadrant both x and y are negative and in the fourth quadrant y is negative and x is positive.